Emulsifying properties of minimally processed Chlamydomonas reinhardtii microalgae ingredients - Julia Baumgartner; Li-Hsuan Lin; Silvan Sgier; Oliver Bolleter; Naomi Arita-Merino; Peter Fischer; Alexander Mathys (Food Research International, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Corrigendum to “A lumped particle direct simulation Monte-Carlo method combined with the collisional-radiative model for simulations of non-equilibrium laser-induced plasma plumes” [Comp. Phys. Comm. 323 (2026) 110090] - Michael A. Stokes; Alexey N. Volkov; Saad A. Khairallah; Alexander M. Rubenchik; Zhibin Lin (Computer Physics Communications, 2026)

Coupled numerical investigation on focused wave interaction with offshore jacket platform and response assessment - Hong Lin; Qi Fan; Shuo Zhang; Kaixin Liang; Alexander Moiseevich Uzdin; Longcheng Wei; Zixuan Lin; Lei Yang (Ocean Engineering, 2026)

Transforming pallet systems for global shipping decarbonization - Tingting Zhang; Hanmo Wang; Zongguo Wen; Lanxin Zhang; Fan Fei; Alexander Lin; Paul Ekins (Environmental Impact Assessment Review, 2026)

A lumped particle direct simulation Monte-Carlo method combined with the collisional-radiative model for simulations of non-equilibrium laser-induced plasma plumes - Michael A. Stokes; Alexey N. Volkov; Saad A. Khairallah; Alexander M. Rubenchik; Zhibin Lin (Computer Physics Communications, 2026)

Redox-active benzo[1,2-b:4,5-b’]dithiophene-4,8-dione-linked conjugated microporous polymers for high-rate, long-life lithium and zinc batteries - Bo-Chen Yeh; Bo-Chun Chen; Ijaz Ali; Sung-En Lin; Trakarn Yimtrakarn; Anton S. Pozdeev; Alexander S. Ivanov; Watchareeya Kaveevivitchai; Ahmed F.M. EL-Mahdy (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Smart turtle farm: soft-shell turtle nesting behavior recognition and monitoring system - Alexander Munyaev; Ben-Lin Jiang; Ing-Jer Huang (Computers and Electronics in Agriculture, 2026)

Rapid Onset and Short Duration of TrenibotulinumtoxinE for Treatment of Moderate to Severe Glabellar Lines: Efficacy and Safety Results from a Phase 3 Study - Marion Moers-Carpi; Cheryl Burgess; Brian Biesman; Deirdre Hooper; Alexander Rivkin; Chung-Yi Chiang; Grace S. Park; Amy Weitzenfeld; Joan-En Chang-Lin (Toxicon, 2026)

Towards low-carbon construction: Nature-inspired internal patterns for thermal insulation in lightweight concrete component cast using 3D-printed formwork - Hanmo Wang; Yujia Wan; Shawn Owyong; En Tian Connie Lim; Abhimanyu Goel; Anqi Shi; Zhuyin Lu; Tam H Nguyen; Harn Wei Kua; Sunmi Shin; Alexander Lin (Energy and Buildings, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Pyrolysis of lime dried sewage sludge in a fixed-bed reactor: Effects of the addition amount of lime - Dan Lin; Wantong Kai; Xing Xie; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Shihong Zhang; Bin Li (Fuel, 2026)

Oxy-ethane combustion: Measurements of the laminar burning velocities and kinetic insights into CO2 effects - Qianjin Lin; Bo Wei; Chun Zou; Alexander A. Konnov (Fuel, 2026)

Drainage volume drives dissolved organic matter leaching loss in a corn system - Xinlin Wang; Diego Arruda Huggins de Sá Leitão; Alexander J. Reisinger; Hardeep Singh; Lakesh Sharma; Yang Lin (Science of The Total Environment, 2025)

Dietary yeast improves zebrafish immunity and survival against Aeromonas infection - Kathiresan Purushothaman; Sérgio D.C. Rocha; Daanish Kaul; Aleksandar B. Goksu; Byron Morales-Lange; Alexander D. Crawford; Liv Torunn Mydland; Henning Sørum; Lin Qingsong; Shubha Vij; Margareth Øverland; Charles McL. Press (Fish & Shellfish Immunology, 2025)

Physics-Informed Graph Neural Networks: Predicting the composite mechanical behavior of clay-infilled concrete structures with morphed honeycomb configurations - Hanmo Wang; Febi Rhiana; Anqi Shi; Zhuyin Lu; Mingkai Li; Tao Wang; Tam H. Nguyen; Alexander Lin (Engineering Structures, 2025)

Styryl lactone derivatives and aristolactam alkaloids from Goniothalamus tapis Miq. and their α-glucosidase inhibitory activity - Piyaporn Phukhatmuen; Passakorn Teerapongpisan; Virayu Suthiphasilp; Tharakorn Maneerat; Thidarat Duangyod; Rawiwan Charoensup; Sarot Cheenpracha; Jin-Lin Zhu; Yan Alexander Wang; Suwanna Deachathai; Raymond J. Andersen; Surat Laphookhieo (Phytochemistry Letters, 2025)

Catalytic pyrolysis of paper mill sludge over self-sourced CaO/biochar catalyst under different temperatures - Wantong Kai; Xing Xie; Dan Lin; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Theoretical basis and analyses of temperature responses of water-saturated rocks to rapid changes in confining pressure - Xiaoqiu Yang; Alexander H.D. Cheng; Weiren Lin; Hehua Xu; Huai Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The impact of wave-induced mixing on the simulation of the upper mixed layer in climate models - Yujie Jing; Jian Sun; Rui Li; Kejian Wu; Zipeng Yu; Pengfei Lin; Xianghui Dong; Alexander V. Babanin (Ocean Modelling, 2025)

Comparative analysis of CO2-based alternative pathways for diphenyl carbonate production - Tsai-Wei Wu; Hajime Ohno; Anqing Wang; Alexander Guzman-Urbina; Yousuke Shinkai; Hiroki Furuhashi; Ryotaro Umezu; Shiang-Tai Lin; Yasuhiro Fukushima (Chemical Engineering Journal, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Styryl lactone derivatives and aristolactam alkaloids from Goniothalamus tapis Miq. and their α-glucosidase inhibitory activity - Piyaporn Phukhatmuen; Passakorn Teerapongpisan; Virayu Suthiphasilp; Tharakorn Maneerat; Thidarat Duangyod; Rawiwan Charoensup; Sarot Cheenpracha; Jin-Lin Zhu; Yan Alexander Wang; Suwanna Deachathai; Raymond J. Andersen; Surat Laphookhieo (Natural Product Research, 2025)

Biomimetic self-shading walls via 3D-printing for reduced heat gain: Multiscale learning using graph neural networks to predict solar radiation absorption - Hanmo Wang; Zhuyin Lu; Amanda Wojtasiak; Shawn Owyong; Bo Sun; Yu Fang; Shahin Vassigh; Alexander Lin (Building and Environment, 2025)

Analysis of main parameters controlling rock avalanche propagation based on machine learning - Ruoshen Lin; Michel Jaboyedoff; Alexander Strom; Marc-Henri Derron; Fengchang Bu (Engineering Geology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Tight ultrafiltration membranes based on engineered metal-monophenolic networks for efficient dye/NaCl separation - Riri Liu; Qin Chen; Jiale Du; Yanyan Liu; Alexander Volodin; Patricia Luis; Wenyuan Ye; Raf Dewil; Ming Xie; Jiuyang Lin; Bart Van der Bruggen (Desalination, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Temporal trend of organic carbon in the East Siberian Arctic shelf sediments and its relation to the recent climate forcing - Jialong Luo; Li Jiang; Limin Hu; Zenghui Yu; Weini Chong; Fudong Lin; Fenghua Su; Yanguang Liu; Kirill Aksentov; Alexander Bosin; Anatolii Astakhov; Xuefa Shi (Acta Oceanologica Sinica, 2025)

Bayesian enhanced graph neural networks: Refining design spaces for hollow concrete components with optimum mechanical performance - Alexander Lin; Hanmo Wang; Wei He; Shawn Owyong; Huan Ting Chen; Tam H. Nguyen (Engineering Structures, 2025)

Western United States wintertime precipitation response to warming: an assessment in a global storm-resolving model - Tsung-Lin Hsieh; Lucas Harris; Kai-Yuan Cheng; Alexander Kaltenbaugh; Linjiong Zhou; Liwei Jia; Ming Zhao (Climate Dynamics, 2025)

A new species of Hoplostethus from Sumatra , eastern Indian Ocean , with comments on its most similar congeners ( Trachichthyiformes : Trachichthyidae ) - Yo Su; Alexander N. Kotlyar; Hsiu‐Chin Lin; Toshio Kawai; Hsuan‐Ching Ho (Journal of Fish Biology, 2025)
A new species of the roughy fish genus Hoplostethus , subgenus Leiogaster , is described based on three specimens collected from Sumatra, Indonesia. This species can be distinguished from its congeners by the following characteristics: gular region covered with ctenoid scales; pelvic‐fin spine smooth on its anterior edge; head depth subequal or smaller than its length (37.2%–38.6% standard length [SL], or 94.7%–99.2% head length [HL]); pectoral‐fin length 35.6%–37.8% SL, reaching beyond a vertical through anal‐fin origin; abdominal scutes well developed, 12–16; pectoral‐fin rays uniformly black, 17–19; gill rakers on the first arch 6–7 + 1 + 13–14 = 21; pre‐dorsal scales 24–27; and pyloric caeca 32. A detailed description is provided along with comparisons with its congeners. Additionally, diagnostic characters of the congeners and literature records of Hoplostethus rubellopterus and Hoplostethus melanopus are discussed.

Numerical study on hydrodynamic characteristics, wave forces and dynamic responses of offshore jacket platform under tsunami-like solitary waves - Hong Lin; Shuo Zhang; Alexander Moiseevish Uzdin; Longcheng Wei; Qi Fan; Lei Yang (Ocean Engineering, 2025)

Acoustic insulation optimization of walls and panels with functional graded hollow sections using graph transformer evaluator and probability-informed genetic algorithm - Hanmo Wang; Tam H Nguyen; Zhuyin Lu; Febi Rhiana; Dickson Fong; Wei He; Shawn Owyong; Huan Ting Chen; Alexander Lin (Building and Environment, 2025)

Effects of elevated oxygen content and temperature on the laminar burning velocity of the blast furnace gas in oxygen-enriched air condition - Xianzhong Hu; Jundie Chen; Qianjin Lin; Alexander A. Konnov (Fuel, 2025)

Experimental and kinetic modeling study of the laminar burning velocity of CH4/H2 mixtures under oxy-fuel conditions - Xianzhong Hu; Jundie Chen; Qianjin Lin; Alexander A. Konnov (Fuel, 2024)

Imaged capillary isoelectric focusing method development for charge variants of high DAR ADCs - Chuan Leng; Shuwen Sun; Wei Lin; Jorge Alexander Pavon; Lynn Gennaro; Rico C. Gunawan; Xiaodong Bu; Tong Yang; Senwu Li (Analytica Chimica Acta, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Crustal-mantle layering deposits in the Von Kármán crater, South Pole-Aitken basin - Zhi Zhong; Yuqi Qian; Chenglong Li; Alexander Y. Sun; Zhongxian Cai; Lei Lin; Xu Guo; Yanbin Kuang; Shiqi Wen; Long Xiao (Earth and Planetary Science Letters, 2024)

Steam gasification of lime dried sewage sludge: Effects of temperature and addition of lime - Dan Lin; Wantong Kai; Xing Xie; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2024)

Assessing the impacts of technological change on food security and climate change mitigation in China’s agriculture and land-use sectors - Xiaoxi Wang; Ruiying Du; Hao Cai; Bin Lin; Jan Philipp Dietrich; Miodrag Stevanović; Hermann Lotze-Campen; Alexander Popp (Environmental Impact Assessment Review, 2024)

Study of a commercial-scale poultry manure oxy-fuel gasification plant via CFD modeling and safety assessment - Qinwen Liu; Yiying Wang; Wei Quan Leong; Yonghua Gu; Alexander Lin; Yuchen Wang; Aibing Yu; Wenqi Zhong; Chi-Hwa Wang (Biomass and Bioenergy, 2024)

Comparative transcriptome analysis provides insights into the resistance regulation mechanism and inhibitory effect of fungicide phenamacril in Fusarium asiaticum - Zhitian Zheng; Huaqi Liu; Xiao Luo; Runze Liu; Alexander Dumbi Joe; Haolin Li; Haiyan Sun; Yanling Lin; Yanzhong Li; Yunpeng Wang (Pesticide Biochemistry and Physiology, 2024)

A CFD-FEA coupled model for simulating dynamic response of offshore jacket platform under earthquake considering wind, wave, current and aftershock loads - Hong Lin; Haochen Luan; Alexander Moiseevish Uzdin; Shuo Zhang; Longcheng Wei; Lei Yang (Ocean Engineering, 2024)

A new correlation between diluent fraction and laminar burning velocities: Example of CH4, NH3, and CH4 + NH3 flames diluted by N2 - Xinlu Han; Hongqing Feng; Riyi Lin; Alexander A. Konnov (Fuel, 2024)

Microplastics in Asian rivers: Geographical distribution, most detected types, and inconsistency in methodologies - Hsin-Tien Lin; Falk Schneider; Muhamad Afiq Aziz; Keng Yinn Wong; Kantha D. Arunachalam; Sarva Mangala Praveena; Sumathi Sethupathi; Woon Chan Chong; Ayu Lana Nafisyah; Purushothaman Parthasarathy; Shreeshivadasan Chelliapan; Alexander Kunz (Environmental Pollution, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

Sediment provenance changes in the southwestern Okhotsk Sea since MIS 5 and their implications for sediment transport dynamics - Anqi Wang; Zhengquan Yao; Xuefa Shi; Kunshan Wang; Yanguang Liu; Jianjun Zou; Yuriy Vasilenko; Fengdeng Shi; Zhi Dong; Xiaojing Wang; Aimei Zhu; Zhengfan Lin; et al. (Global and Planetary Change, 2024)

Efficacy and Safety of a Novel Formulation Liquid Botulinum Toxin, RelabotulinumtoxinA, When used for Combination Treatment of Glabellar and Lateral Canthal Lines - Vince Bertucci; Joel Schlessinger; John Joseph; Ava Shamban; Z. Paul Lorenc; Robert Weiss; Leslie Baumann; Mark S. Nestor; Heidi B. Prather; Derek Jones; Alexander S. Donath; Rebecca Kazin; et al. (Toxicon, 2024)

Intimately tracking NO2 pollution over the New York City - Long Island Sound land-water continuum: An integration of shipboard, airborne, satellite observations, and models - Maria Tzortziou; Christopher P. Loughner; Daniel L. Goldberg; Laura Judd; Dilchand Nauth; Charlotte F. Kwong; Tong Lin; Alexander Cede; Nader Abuhassan (Science of The Total Environment, 2023)

Cenozoic mantle plume activity in East Asia: Constraints from geochemistry of olivine, spinel, and melt inclusions - Sheng-Peng Wang; Zhong-Yuan Ren; Alexander R.L. Nichols; Tserendash Narantsetseg; Qing-Lin Zhang; Le Zhang; Chao Yuan (Lithos, 2023)

Trace analysis of per- and polyfluorinated alkyl substances (PFAS) in dried blood spots – Demonstration of reproducibility and comparability to venous blood samples - Elizabeth Z. Lin; Sara L. Nason; Alexander Zhong; John Fortner; Krystal J. Godri Pollitt (Science of The Total Environment, 2023)

The role of harmonized Landsat Sentinel-2 (HLS) products to reveal multiple trajectories and determinants of cropland abandonment in subtropical mountainous areas - Changqiao Hong; Alexander V. Prishchepov; Xiaobin Jin; Bo Han; Jinhuang Lin; Jingping Liu; Jie Ren; Yinkang Zhou (Journal of Environmental Management, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

Microplastics in rivers along an urban-rural gradient in an urban agglomeration: Correlation with land use, potential sources and pathways - Alexander Kunz; Falk Schneider; Nixon Anthony; Hsin-Tien Lin (Environmental Pollution, 2023)

The TCI Clinical Encounter Program for PhD Students in Cancer Biology: a Feasibility Pilot - Alexander M. Real; Jenny J. Lin; Janice L. Gabrilove (Journal of Cancer Education, 2023)
Clinical rotations are often not included in graduate-level cancer biology curricula; however, basic insight into clinical oncology is often crucial for developing translational research that addresses unmet needs with the potential to benefit cancer patients. We describe a needs assessment, design, implementation, and descriptive evaluation of an oncology-specific pilot clinical encounter program developed for PhD students in the Cancer Biology Training Area (CAB) in the Graduate School of Biomedical Sciences (GSBS) and Tisch Cancer Institute (TCI) at the Icahn School of Medicine at Mount Sinai (ISMMS). Prior to the development of this pilot program, CAB students, in years 2–5 + , were surveyed to determine their interest in a structured clinical experience. Seventeen out of thirty-one students responded (55%) to the survey. Of those seventeen respondents, fifteen (88.2%) expressed that exposure to cancer patients in the clinical setting would be useful for their pre-doctoral biomedical science and cancer biology training and indicated an interest in participating in the clinical encounter program. Based on these responses, a three-session clinical encounter pilot program was designed. Two separate cohorts of 5 students participated in this pilot program. During a formal debrief, following the clinical experience, students commented on the resilience of patients and the importance of research on clinical decision making, and reported that they found the experience motivational. Five out of 10 students responded (50%) to a post-program assessment survey; all five respondents answered that they would recommend the clinical encounter program to their peers. While limited in size and scope, this pilot TCI Clinical Encounter Program proved feasible and has the potential to enrich and inform the experience of PhD students pursing advanced degrees in a cancer biology.

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Correction to: Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)

Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)
Reactive nitrogen (N) is a requisite nutrient for agricultural production, but results in greenhouse gas and air and water pollution. The environmental and economic impacts of N fertilizer use in China are particularly relevant, as China consumes the largest amount of N fertilizer in the world to meet its soaring food demand. Here, we use an agro-economic land system model (MAgPIE) in combination with a difference-in-differences econometric model to provide a forward-looking assessment of China’s fertilizer policies in terms of removing fertilizer manufacturing subsidies and implementing measures to improve agricultural nutrient management efficiency. Our model results indicate that enhancing soil N uptake efficiency and manure recycled to soil alongside fertilizer subsidy removal can largely reduce N fertilizer use and N losses and abate N pollution in the short and long term, while food security remains largely unaffected. Enhancing soil N uptake efficiency appears to be decisive to achieving China’s national strategic target of zero growth in N fertilizer use. This study also finds that improving agricultural nutrient management efficiency contributes to higher land productivity and less cropland expansion, with substantial benefits for the environment and food security.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Engineering osteoarthritic cartilage model through differentiating senescent human mesenchymal stem cells for testing disease-modifying drugs - Ning Wang; Yuchen He; Silvia Liu; Meagan J. Makarcyzk; Guanghua Lei; Alexander Chang; Peter G. Alexander; Tingjun Hao; Anne-Marie Padget; Nuria de Pedro; Tsapekos Menelaos; Hang Lin (Science China Life Sciences, 2022)

Current management of melanoma patients with nodal metastases - Dale Han; Alexander C. J. van Akkooi; Richard J. Straker; Adrienne B. Shannon; Giorgos C. Karakousis; Lin Wang; Kevin B. Kim; Douglas Reintgen (Clinical & Experimental Metastasis, 2022)

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer - Inga K. Koerte; Roald Bahr; Peter Filipcik; Jolien Gooijers; Alexander Leemans; Alexander P. Lin; Yorghos Tripodis; Martha E. Shenton; Nir Sochen; Stephan P. Swinnen; Ofer Pasternak (Brain Imaging and Behavior, 2022)
Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RHI, or about the risk factors that may lead to clinical or behavioral sequelae. REPIMPACT is a prospective longitudinal study of competitive youth soccer players and non-contact sport controls aged 14 to 16 years. The study aims to characterize consequences of exposure to RHI with regard to behavior (i.e., cognition, and motor function), clinical sequelae (i.e., psychiatric and neurological symptoms), brain structure, function, diffusion and biochemistry, as well as blood- and saliva-derived measures of molecular processes associated with exposure to RHI (e.g., circulating microRNAs, neuroproteins and cytokines). Here we present the structure of the REPIMPACT Consortium which consists of six teams of clinicians and scientists in six countries. We further provide detailed information on the specific aims and the design of the REPIMPACT study. The manuscript also describes the progress made in the study thus far. Finally, we discuss important challenges and approaches taken to overcome these challenges.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Binding of gephyrin to microtubules is regulated by its phosphorylation at Ser270 - Lin Zhou; Eva Kiss; Rebecca Demmig; Joachim Kirsch; Ralph Alexander Nawrotzki; Jochen Kuhse (Histochemistry and Cell Biology, 2021)
Gephyrin is a multifunctional scaffolding protein anchoring glycine- and subtypes of GABA type A- receptors at inhibitory postsynaptic membrane specializations by binding to the microtubule (MT) and/or the actin cytoskeleton. However, the conditions under which gephyrin can bind to MTs and its regulation are currently unknown. Here, we demonstrate that during the purification of MTs from rat brain by sedimentation of polymerized tubulin using high-speed centrifugation a fraction of gephyrin was bound to MTs, whereas gephyrin phosphorylated at the CDK5-dependent site Ser270 was detached from MTs and remained in the soluble protein fraction. Moreover, after collybistin fostered phosphorylation at Ser270 the binding of a recombinant gephyrin to MTs was strongly reduced in co-sedimentation assays. Correspondingly, upon substitution of wild-type gephyrin with recombinant gephyrin carrying alanine mutations at putative CDK5 phosphorylation sites the binding of gephyrin to MTs was increased. Furthermore, the analysis of cultured HEK293T and U2OS cells by immunofluorescence-microscopy disclosed a dispersed and punctuated endogenous gephyrin immunoreactivity co-localizing with MTs which was evidently not phosphorylated at Ser270. Thus, our study provides additional evidence for the binding of gephyrin to MTs in brain tissue and in in vitro cell systems. More importantly, our findings indicate that gephyrin-MT binding is restricted to a specific gephyrin fraction and depicts phosphorylation of gephyrin as a regulatory mechanism of this process by showing that soluble gephyrin detached from MTs can be detected specifically with the mAb7a antibody, which recognizes the Ser270 phosphorylated- version of gephyrin.

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Modeling motor task activation from resting-state fMRI using machine learning in individual subjects - Chen Niu; Alexander D. Cohen; Xin Wen; Ziyi Chen; Pan Lin; Xin Liu; Bjoern H. Menze; Benedikt Wiestler; Yang Wang; Ming Zhang (Brain Imaging and Behavior, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Human skin-derived ABCB5+ stem cell injection improves liver disease parameters in Mdr2KO mice - Vanessa Hartwig; Bedair Dewidar; Tao Lin; Anne Dropmann; Christoph Ganss; Mark Andreas Kluth; Nils Tappenbeck; Lysann Tietze; Bruno Christ; Markus Hermann Frank; Roger Vogelmann; Matthias Philip Alexander Ebert; et al. (Archives of Toxicology, 2019)

Human skin-derived ABCB5+ stem cell injection improves liver disease parameters in Mdr2KO mice - Vanessa Hartwig; Bedair Dewidar; Tao Lin; Anne Dropmann; Christoph Ganss; Mark Andreas Kluth; Nils Tappenbeck; Lysann Tietze; Bruno Christ; Markus Frank; Roger Vogelmann; Matthias Philip Alexander Ebert; et al. (Archives of Toxicology, 2019)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Bacillus Probiotic Supplementations Improve Laying Performance, Egg Quality, Hatching of Laying Hens, and Sperm Quality of Roosters - Maria S. Mazanko; Ivan F. Gorlov; Evgeniya V. Prazdnova; Maxim S. Makarenko; Alexander V. Usatov; Anzhelika B. Bren; Vladimir A. Chistyakov; Alexey V. Tutelyan; Zoya B. Komarova; Natalia I. Mosolova; Denis N. Pilipenko; Olga E. Krotova; et al. (Probiotics and Antimicrobial Proteins, 2018)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Plant adaptation or acclimation to rising CO 2 ? Insight from first multigenerational RNA‐Seq transcriptome - Alexander Watson‐Lazowski; Yunan Lin; Franco Miglietta; Richard J. Edwards; Mark A. Chapman; Gail Taylor (Global Change Biology, 2016)
Atmospheric carbon dioxide ( CO 2 ) directly determines the rate of plant photosynthesis and indirectly effects plant productivity and fitness and may therefore act as a selective pressure driving evolution, but evidence to support this contention is sparse. Using Plantago lanceolata L. seed collected from a naturally high CO 2 spring and adjacent ambient CO 2 control site, we investigated multigenerational response to future, elevated atmospheric CO 2 . Plants were grown in either ambient or elevated CO 2 (700 μmol mol −1 ), enabling for the first time, characterization of the functional and population genomics of plant acclimation and adaptation to elevated CO 2 . This revealed that spring and control plants differed significantly in phenotypic plasticity for traits underpinning fitness including above‐ground biomass, leaf size, epidermal cell size and number and stomatal density and index. Gene expression responses to elevated CO 2 (acclimation) were modest [33–131 genes differentially expressed ( DE )], whilst those between control and spring plants (adaptation) were considerably larger (689–853 DE genes). In contrast, population genomic analysis showed that genetic differentiation between spring and control plants was close to zero, with no fixed differences, suggesting that plants are adapted to their native CO 2 environment at the level of gene expression. An unusual phenotype of increased stomatal index in spring but not control plants in elevated CO 2 correlated with altered expression of stomatal patterning genes between spring and control plants for three loci ( YODA , CDKB 1;1 and SCRM 2 ) and between ambient and elevated CO 2 for four loci ( ER , YODA , MYB 88 and BCA 1 ). We propose that the two positive regulators of stomatal number ( SCRM 2 ) and CDKB 1;1 when upregulated act as key controllers of stomatal adaptation to elevated CO 2 . Combined with significant transcriptome reprogramming of photosynthetic and dark respiration and enhanced growth in spring plants, we have identified the potential basis of plant adaptation to high CO 2 likely to occur over coming decades.

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Multiplexed Fluid Flow Device to Study Cellular Response to Tunable Shear Stress Gradients - Maggie A. Ostrowski; Eva Y. Huang; Vinay N. Surya; Charlotte Poplawski; Joseph M. Barakat; Gigi L. Lin; Gerald G. Fuller; Alexander R. Dunn (Annals of Biomedical Engineering, 2016)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

A petrologic, geochemical and Sr–Nd isotopic study on contact metamorphism and degassing of Devonian evaporites in the Norilsk aureoles, Siberia - Kwan-Nang Pang; Nicholas Arndt; Henrik Svensen; Sverre Planke; Alexander Polozov; Stephane Polteau; Yoshiyuki Iizuka; Sun-Lin Chung (Contributions to Mineralogy and Petrology, 2013)

Rapid decrease in tumor perfusion following VEGF blockade predicts long-term tumor growth inhibition in preclinical tumor models - Alexandra Eichten; Alexander P. Adler; Blerta Cooper; Jennifer Griffith; Yi Wei; George D. Yancopoulos; Hsin Chieh Lin; Gavin Thurston (Angiogenesis, 2013)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Spatial Frequency Domain Imaging of Intrinsic Optical Property Contrast in a Mouse Model of Alzheimer’s Disease - Alexander J. Lin; Maya A. Koike; Kim N. Green; Jae G. Kim; Amaan Mazhar; Tyler B. Rice; Frank M. LaFerla; Bruce J. Tromberg (Annals of Biomedical Engineering, 2011)

Protection against HIV-envelope-induced neuronal cell destruction by HIV attachment inhibitors - Sharon Zhang; Louis Alexander; Tao Wang; Michele Agler; Nannon Zhou; Hua Fang; John Kadow; Paul Clapham; Pin-Fang Lin (Archives of Virology, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Targeted and systemic radiotherapy in the treatment of bone metastasis - Alexander Lin; Michael E. Ray (Cancer and Metastasis Reviews, 2007)

Genetic and transgenic perturbations of carbon reserve production in Arabidopsis seeds reveal metabolic interactions of biochemical pathways - Yun Lin; Alexander V. Ulanov; Vera Lozovaya; Jack Widholm; Guirong Zhang; Jinhua Guo; Howard M. Goodman (Planta, 2006)

Spectral and Kinetic Analysis of the Energy Coupling in the PS I–LHC I Supercomplex from the Green Alga Chlamydomonas reinhardtii at 77 K - Alexander N. Melkozernov; Joanna Kargul; Su Lin; James Barber; Robert E. Blankenship (Photosynthesis Research, 2005)

Making thin polymeric materials, including fabrics, microbicidal and also water-repellent - Jian Lin; Shashi K. Murthy; Bradley D. Olsen; Karen K. Gleason; Alexander M. Klibanov (Biotechnology Letters, 2003)

Insights into bactericidal action of surface-attached poly(vinyl-N-hexylpyridinium) chains - Jian Lin; Joerg C. Tiller; Sang Beom Lee; Kim Lewis; Alexander M. Klibanov (Biotechnology Letters, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Fine scale mapping places DLG1, the gene encoding hDlg, telomeric to the OPA1 candidate region - Christiane Alexander; Dean G. Stathakis; Lunhui Lin; Shayan Rahman; Peter J. Bryant; Georg Auburger; Athar H. Chishti (Mammalian Genome, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)